Morphological-and Microstructural Evolution and Related Impurity Incorporation in Non-Polar a-Plane GaN Grown on r-Sapphire Substrates - 蒋仁渊 许晟瑞 张进成 姜腾 江海清 王之哲 樊永祥 郝跃 (Chinese physics letters, 2015)
Effects of the growth temperature on morphological and microstructural evolution of a-plane GaN films grown on r-plane sapphires by metal organic chemical vapor deposition are investigated by atomic force microscopy and secondary ion mass spectroscopy （SIMS）. Surface morphology, structural quality and related impurity incorpora- tion are very sensitive to the growth temperature. A significant difference of yellow luminescence is observed and attributed to the incorporation of carbon into GaN films, which is confirmed by SIMS analysis. Our results show that the sample with triangular-pit morphology has sample with pentagon-like pit morphology, which is significantly higher concentrations of oxygen than the other induced by the existence of an N-face in triangular pits.